Avaliação da resistência e da deformabilidade de quatro solos empregados em subleitos rodoviários no estado do Rio Grande do Sul - Santos, Thaís Aquino dos (2016)
The pavement is considered a finite multiple layer system, subject to stresses, strains and displacements from the cyclical traffic requests. The subgrade, as it is the foundation of a pavement structure, must have a support capacity compatible with the intensity and frequency with which it is requested. So, it is fundamental the study of the behavior of soils used as subgrade materials, especially through its resistance and deformability, as well as the factors that influence these properties. The main objective of this study is to evaluate the behavior of four soils with different geological origin, considering its resistance and deformability, for employment in road subgrades in the state of Rio Grande do Sul. The methodology used in this study consists of physical and mechanical testing, chemical analysis, obtainment of the characteristic curves of the soils, direct shear strength tests and triaxial tests with repeated loads. Besides the complete characterization of these, it was performed numerical simulations, to assess the performance of soils under study in the foundation of a standard pavement, dimensioned through the DNIT method. The limits described in standard for use of the soils as a subgrade material were satisfied, showing expansion values lower than 2% and California Bearing Ratio- CBR ranging from 10% to 16%. The resilience modules were obtained by triaxial tests with repeated loads, being the compound model the one that best describes the resilient behavior of soils, because it considers the state of stresses acting on the structure. In addition to the evaluation of the shear strength of the soil, it was also evaluated the influence of moisture content on this property. In general, analyzing the Mohr failure line there is a reduction in the shear strength of the material with moisture addition. With a reduction of 2% in the optimal content, the shear strength of these increases considerably. The mechanistic analysis, carried out with the help of AEMC tool and the software AASHTOWare Pavement ME Design, allowed to assess the mechanical response of the soil when used in subgrade of a pavement, besides highlighting the importance of resilient modulus behavior of the structure as a whole.